Internalizing Mental Disorders and Accelerated Cellular Aging Among Perinatally HIV-Infected Youth in Uganda - Kalungi, Allan; Womersley, Jacqueline S.; Kinyanda, Eugene; Joloba, Moses L.; Ssembajjwe, Wilber; Nsubuga, Rebecca N.; Levin, Jonathan; Kaleebu, Pontiano; Kidd, Martin; Seedat, Soraya; Hemmings, Sian M. J. (Frontiers in Genetics, 2019)
Introduction: Internalizing mental disorders (IMDs) in HIV+ children and adolescents are associated with impaired quality of life and non-adherence to anti-retroviral treatment. Telomere length is a biomarker of cellular aging, and shorter telomere length has been associated with IMDs. However, the nature of this association has yet to be elucidated. Objective: We determined the longitudinal association between IMDs and relative telomere length (rTL) and the influence of chronic stress among Ugandan perinatally HIV-infected youth (PHIY). Methods: IMDs (depressive disorders, anxiety disorders, and post-traumatic stress disorder) and IMDs were assessed using the locally adapted Child and Adolescent Symptom Inventory-5. In 368 PHIY with any IMD and 368 age- and sex-matched PHIY controls without any psychiatric disorder, rTL was assessed using quantitative polymerase chain reaction. Hierarchical cluster analysis was used to generate the three chronic stress classes (mild, moderate, and severe). t-tests were used to assess the difference between baseline and 12 month rTL and the mean difference in rTL between cases and controls both at baseline and at 12 months. Linear regression analysis was used to model the effects of chronic stress on the association between IMDs and rTL, controlling for age and sex. Results: We observed longer rTL among cases of IMDs compared with controls (p < 0.001). We also observed a statistically significant reduction in rTL between baseline and 12 months in the combined sample of cases and controls (p < 0.001). The same statistical difference was observed when cases and controls were individually analyzed (p < 0.001). We found no significant difference in rTL between cases and controls at 12 months (p = 0.117). We found no significant influence of chronic stress on the association between IMDs and rTL at both baseline and 12 months. Conclusion: rTL is longer among cases of IMDs compared with age- and sex-matched controls. We observed a significant attrition in rTL over 12 months, which seems to be driven by the presence of any IMDs. There is a need for future longitudinal and experimental studies to understand the mechanisms driving our findings.